Psychological stress and influencing factors of hospital workers in different periods under the public health background of infectious disease outbreak: A cross‐sectional study - Xing Miao; Wei Wang; Yongli Chen; Xiufang Huang; Rehua Wang (Health Science Reports, 2022)
Abstract Background and Aims It is well known that public health emergencies can affect the mental health of medical personnel, and many studies have focused on cross‐sectional studies with short‐term benefits. The present study aimed to investigate the long‐term influence of infectious disease outbreak about the mental health of hospital staff. Methods The demographic characteristics and mental health status of staff in Fuzhou, China, were analyzed by using the Generalized Anxiety Disorder (GAD‐7) Scale and Depression Screening Scale (9‐item Patient Health Questionnaire [PHQ‐9]) in February and December 2020. Results There were no significant differences in anxiety levels during different time periods (p > 0.05), but there were significant differences among anxiety level and total score of GAD‐7 scale (p < 0.001). There were significant differences among the number of people with depression, depression level, and total score on the PHQ‐9 scale (p < 0.001). As the pandemic progressed, total scores of anxiety in medical staff with different titles decreased (p < 0.05), but depression scores in professionals with intermediate and senior titles increased significantly (p < 0.05). changes in anxiety and depression scores during different time periods also changed according to hospital worker specialty. Total scores of anxiety in doctors, nurses, medical technicians, and other staff members all decreased (p < 0.05), while total scores of depression in doctors, nurses, and other staff members significantly increased (p < 0.05). There were no significant differences in total depression score among medical technicians (p > 0.05). Conclusions Since the outbreak of an infectious disease public health emergency, the anxiety of hospital staff has decreased over time, but the depression has increased. The management and psychological support personnel in medical institutions should continue to pay attention to the mental health of medical staff, and it is necessary to take different intervention measures in different periods when implementing the psychological crisis prevention mechanism.